1997
DOI: 10.1016/s0169-5150(97)00007-8
|View full text |Cite
|
Sign up to set email alerts
|

Identifying international rice research spillovers in New South Wales

Abstract: The rice industry in New South Wales, Australia, has benefited from the international flow of germplasm, as have other industries. The aim in this paper is to identify those international flows, and to value their contributions to the industry. Analysis is made of the origins and pedigrees of the rice varieties grown in New South Wales since the 1960s, and the contribution of different germplasm sources are identified, using the geometric rule of partitioning contributions. The analysis reveals that New South … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Pardey et al (1996) evaluated data from two centers of CGIAR, reporting benefit and cost ratios of 48:1 for rice and 190:1 for wheat. Brennan et al (1997) suggested that 64% of the gains from rice breeding in Australia were due to the acquisition of international germplasm, generating benefits of US$ 848 million. Evenson and Gollin (1997) estimated that without the efforts of an international network for evaluation of rice germplasm, 20 new commercial varieties would not have been developed.…”
Section: Ll Nass Et Almentioning
confidence: 99%
“…Pardey et al (1996) evaluated data from two centers of CGIAR, reporting benefit and cost ratios of 48:1 for rice and 190:1 for wheat. Brennan et al (1997) suggested that 64% of the gains from rice breeding in Australia were due to the acquisition of international germplasm, generating benefits of US$ 848 million. Evenson and Gollin (1997) estimated that without the efforts of an international network for evaluation of rice germplasm, 20 new commercial varieties would not have been developed.…”
Section: Ll Nass Et Almentioning
confidence: 99%
“…Another was how to partition credit for Embrapa releases in proportion to shares of funding support between Embrapa and its public-and private-sector partners in joint-venture projects. Using a geometric attribution rule, the authors found that, of the total 21 Other studies that used genetic attribution rules to measure country-to-country spillovers of varietal technologies include Flores- Moya et al (1978), Evenson (1994), Brennan et al (1997), Maredia and Byerlee (2000), and Jin et al (2002), for example. benefits from varietal improvement for upland rice in Brazil (which had a present value of US$1683 million in 1999 dollars over [1984][1985][1986][1987][1988][1989][1990][1991][1992][1993][1994][1995][1996][1997][1998][1999][2000][2001][2002][2003], non-Embrapa sources were responsible for 64 per cent.…”
Section: Spillover Impacts In Ex-post Models Of Specific Commoditiesmentioning
confidence: 99%
“…The similarity of such agroclimatic conditions between the locations where technologies are developed and the areas where they are used (agroclimatic similarity hereafter), may shorten “technological distance” (Evenson and Westphal, ; Griliches, ) which then raise the performances of these technologies and agricultural productivity where they are used. The importance of such similarity and its effects on spillover potentials is recognized in the literature, particularly in developed countries (Alston, ; Alston et al., ; Brennan et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…More broadly, we also contribute to the earlier studies investigating the effects of agricultural R&D on agricultural productivity around the world (Craig et al., ; Fan and Pardey, ), as well as SSA (Alene et al., ; Alene, ) by providing further evidence on Nigeria from the angle of agroclimatic similarity. In doing so, we provide more contextual insights into the roles of agroclimatic similarity and spillovers (Alston, ; Alston et al., ; Brennan et al., ; Evenson and Westphal, ; Griliches, ; Maredia et al., ; You and Johnson, ).…”
Section: Introductionmentioning
confidence: 99%